Studi Literatur: Efektifitas Word Wall dalam Mata Pelajaran Pendidikan Agama Islam di Sekolah Dasar - Baen, Faldin (Diniyah: Jurnal Pendidikan Dasar, 2022)
Education requires a technological approach to create an interesting and up-to-date learning process. Wordwall is a modern application that provides attractive templates to make it easier for PAI teachers to carry out the learning process. This research aims to present the effectiveness of wordwalls in learning Islamic Religious Education. Another goal is to create an interesting learning process for students in the classroom. The research method is carried out in the form of a literature study by collecting various journals, books and other scientific data related to the research topic. This research found that wordwalls can be used as learning media for Islamic religious education in the classroom. The wordwall application has an important role in creating an interesting, enjoyable learning atmosphere and creates enthusiasm in children. Wordwall also creates good imagination in children, making students always interested in taking part in the next PAI lesson. Keywords: Literature study, wordwall, PAI learning